Pengaruh Manajemen Sarana Prasarana dan Iklim Sekolah Terhadap Kinerja Guru - Delia Putri, Anggun; Zebua, Ali Marzuki (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2025)
This study aims to analyze the effect of infrastructure management and school climate on teacher performance at SDN 015/II Lawang Agung. Effective management of infrastructure facilities and a conducive school climate are considered as external factors that can encourage the improvement of the quality of teacher work in the learning process. This study used a quantitative approach with a survey method of 52 teachers as respondents, who were selected through a simple random sampling technique. The research instrument is a closed questionnaire that has been tested for validity and reliability (Cronbach's Alpha value: X₁ = 0.854; X₂ = 0.804; Y = 0.784). The results of data analysis show that both infrastructure management (X₁) and school climate (X₂) have a significant effect on teacher performance (Y). The t-test results show the t_count value for X₁ = 2.750 (sig. 0.008) and X₂ = 3.940 (sig. 0.000), both greater than t_table = 2.010, indicating a significant effect partially. The F test also shows a highly significant simultaneous effect with a value of F_hitung = 59.524> F_tabel = 3.19 (sig. 0.000). The coefficient of determination (Adjusted R²) of 0.697 indicates that 69.7% of the variation in teacher performance can be explained by the two independent variables together, while the remaining 30.3% is influenced by other factors outside the research model. In addition, Pearson correlation analysis shows a strong and positive relationship between infrastructure management and teacher performance